Outcome prediction in mechanically ventilated neurologic patients by junior neurointensivists [Image: see text] - Finley Caulfield, A. (American Academy of Neurology, 2010)
OBJECTIVE: Physician prediction of outcome in critically ill neurologic patients impacts treatment decisions and goals of care. In this observational study, we prospectively compared predictions by neurointensivists to patient outcomes at 6 months. METHODS: Consecutive neurologic patients requiring mechanical ventilation for 72 hours or more were enrolled. The attending neurointensivist was asked to predict 6-month 1) functional outcome (modified Rankin scale [mRS]), 2) quality of life (QOL), and 3) whether supportive care should be withdrawn. Six-month functional outcome was determined by telephone interviews and dichotomized to good (mRS 0–3) and poor outcome (mRS 4–6). RESULTS: Of 187 eligible patients, 144 were enrolled. Neurointensivists correctly predicted 6-month functional outcome in 80% (95% confidence interval [CI], 72%–86%) of patients. Accuracy for a predicted good outcome was 63% (95% CI, 50%–74%) and for poor outcome 94% (95% CI, 85%–98%). Excluding patients who had life support withdrawn, accuracy for good outcome was 73% (95% CI, 60%–84%) and for poor outcome 87% (95% CI, 74%–94%). Accuracy for exact agreement between neurointensivists' mRS predictions and actual 6-month mRS was only 43% (95% CI, 35%–52%). Predicted accuracy for QOL was 58% (95% CI, 39%–74%) for good/excellent and 67% (95% CI, 46%–83%) for poor/fair. Of 27 patients for whom withdrawal of care was recommended, 1 patient survived in a vegetative state. CONCLUSIONS: Prediction of long-term functional outcomes in critically ill neurologic patients is challenging. Our neurointensivists were more accurate in predicting poor outcome than good outcome in patients requiring mechanical ventilation ≥72 hours. GLOSSARY: BI: = Barthel index; CI: = confidence interval; E-GOS: = extended Glasgow outcome scale score; ICU: = intensive care unit; IQR: = interquartile range; mRS: = modified Rankin scale; QOL: = quality of life.